Public finance reform during the transition : the experience of Hungary - Bokros, Lajos; Dethier, Jean-Jacques (Washington, D.C. : World Bank, 1998)
This volume aims to provide comprehensive description of one country's experience of public finance reform in a former socialist economy. The book focuses on Hungary, an early reformer that underwent a profound- and still unfinished - process of transformation.
Includes bibliographical references and index.
osc 22/07/16
Loans
Keywords: Finance, Public